The Tadpole of Batrachophrynus patagonicus Gallardo - Cei, José Miguel Alfredo María (1965)
In the course of his study on Argentinian batrachians, Gallardo (1962) described a new leptodactylid frog inhabiting the isolated sub-Andean Laguna Blanca (Neuquen Province: 70°2(y W. 30°03' S.). He designated the frog Batrachophrynus patagonicus, and believed it to be closely related to the specialized Telmatobiinae from the Peruvian plateau. The frogs of this group are of special biogeographical interest, since the newly recognized Patagonian species is from a locality about 2,000 miles south of B. macrostomus and br achy dactylus from the Junin lagoons of Peru. The tadpoles of patagonicus are still undescribed, and little is known concerning diagnostic characters and variation of the larval stages of the related Peruvian species. Our recent collections (January, 1964) at the isolated type-locality of patagonicus provided an opportunity for a preliminary study of larval characters of this species. Some ecological notes on the adults and larvae are reported in the present paper.